Today's Shifting Cultivation and its Impact on Forest and Environmental Damage in Routa, Konawe, Southeast Sulawesi - Sarlan Adijaya (Jurnal Penelitian Pendidikan IPA, 2024)
This article is intended to explore and analyze some of the impacts of shifting cultivation to the forest environmental degradation in Routa today. This study uses a combination of qualitative and quantitative research approaches, especially with the rational equation methods where the results of statistical calculations are then culturally interpreted. The results of this study indicate that current shifting cultivation has contributed greatly to the increasing damage to the forest environment and decreased hydro-urologic functions of forests in Routa as well as other ecological functions, including conversion of primary and secondary forest land to shifting cultivation areas, restoration of areas ex-shifting cultivation that are ongoing slower than usual, increased surface water flow, increased erosion, and sedimentation, increased local air temperature and decreased humidity and the potential for large carbon losses.